ANALISIS TINGKAT PERPUTARAN PIUTANG STUDI PADA PT XYZ PERUSAHAAN MANUFAKTUR DI GRESIK - Fatimatuz Zahroh; Anita Handayani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the analysis of the receivable turnover rate at PT XYZ in 2018-2021. Accounts receivable turnover analysis is very important to know the receivables turnover of the company. This research was conducted at PT XYZ. The analytical method used in this research is using a qualitative approach with descriptive research methods, Using Receivable Turna Over (RTO) analysis, Average Collection Period (ACP), Non-Performing Loans (NPL), and, Billing Ratio. The results of this study indicate that the management of receivables at PT XYZ is experiencing instability (up and down). So that the management of the company's receivables needs to be improved again. This Non Performing Loan (NPL) ratio shows that the NPL in 2019 and 2021 is not healthy. The company's Average Collection Period (ACP) value in 2018 was 45 days, in 2019 it was 54 days, in 2021 it was 45 days and in 2021 it was 122 days, so the company's ACP was declared low. Meanwhile, the Billing Ratio in 2020 increased compared to other years, where in 2020 the company was able to collect well and experienced a decline in 2021 to 37%.